2016
DOI: 10.1188/16.onf.235-243
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Toxicity of Tyrosine Kinase Inhibitors

Abstract: Purpose/Objectives To review common tyrosine kinase inhibitors, as well as their ocular side effects and management. Data Sources A comprehensive literature search was conducted using cINahl®, Pubmed, and cochrane databases for articles published since 2004 with the following search terms: ocular toxicities, tyrosine kinase inhibitors, ophthalmology, adverse events, eye, and vision. Data Synthesis Tyrosine kinase inhibitors can cause significant eye toxicity. Conclusions Given the prevalence of new tyros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 29 publications
0
16
1
Order By: Relevance
“… 18 21 Ocular toxicities have been reported with FGFR inhibitors. 22 In this study, only a single case of grade 3 punctate keratitis was reported with ODM-203 and was classified as a DLT after administration of an 800 mg dose. Most of the ocular events reported with ODM-203 (19.0%) were mild in severity, with conjunctivitis being the most frequently reported event.…”
Section: Discussionmentioning
confidence: 80%
“… 18 21 Ocular toxicities have been reported with FGFR inhibitors. 22 In this study, only a single case of grade 3 punctate keratitis was reported with ODM-203 and was classified as a DLT after administration of an 800 mg dose. Most of the ocular events reported with ODM-203 (19.0%) were mild in severity, with conjunctivitis being the most frequently reported event.…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies have reported that systemic anticancer therapies with TKIs cause ocular complications, including acute and chronic damage to the eye. 44 Interestingly, however, several TKIs, including human epidermal growth factor receptor 2 inhibitors and epidermal growth factor receptor inhibitors, have been reported to cause ophthalmic side effects, such as dry eye syndrome, whereas the two common ocular side-effects related to imatinib are periorbital edema and epiphora. 45 In this regard, it should be noted that the beneficial effect on DED in animal models can be obtained with a low dose of imatinib compared with the human equivalent dose that is currently used for anti-cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the fact that nearly 90% of the genome is expressed in the tissues of the eye, there are many molecular cross-reactive targets for kinase inhibitors [ 76 ]. Toxicity can be idiosyncratic and may range from mild conjunctivitis to optic disc edema and optic neuritis which have been noted in patients treated with dasatinib, imatinib, and nilotinib [ 77 ]. A rare toxicity of EGFR inhibitor therapy includes trichomegaly, or abnormal growth of the eyelashes, which can lead to back-growth of the lashes onto the conjunctiva and cornea, leading to corneal ulcerations in severe cases [ 78 ].…”
Section: Methodsmentioning
confidence: 99%